AVICENNA'S INFORMATION ABOUT THE HEALING PROPERTIES OF BLACK SEED - YU.N. NURALIEV; R.A. RAKHMONOV; M.T. GANIEVA; L.YU. NURALIEV (Avicenna Tajik State Medical University, 2020)
The end of the 20th and the beginning of the 21st centuries in modern medicine can be called the era of the second birth and large-scale phytochemical and pharmacological study of black seed (Nigella sativa L. ). Today, the experience of the famous doctor and encyclopedist Avicenna on the clinical use of herbal medicines, created on the basis of black seed, can be a boost for their safe use against many severe human diseases. Nigella sativa L. is considered to be an ancient medicinal preparation of Eastern medicine. In this review, we analyzed five books, «The Canon of Medical Science», some other medicinal treatises of Avicenna, as well as modern studies on therapeutic properties and practical applications of black seed. Collected information from various books of the scientist were subjected to pharmacological, phytochemical and biochemical screening.